Civil Service Reform – Expectations Related to the Implementation of The National Recovery and Resilience Plan (NRRP) - Alunica Morariu (Ovidius University Annals: Economic Sciences Series, 2024)
In various analyzes of the European institutions, including in the document related to the European Semester 2020, it is found that the progress in the reform of the public administration in Romania is limited in terms of the decision-making process, the quality and the effective use of the evaluations of the impact of the regulations. Also, an effective framework for strategic and budgetary planning in the field of public administration has not yet been created. Frequent reorganizations and the excessive use of temporary management instead of contests for the appointment of managers hinder the independence of the administration.Excessive bureaucracy and diminished possibilities for providing high-quality public services negatively influence the life of the citizen and the business environment. All these aspects highlight the need for a genuine reform of the civil service. The purpose of this paper is related to the study of the expectations generated by the civil service reform in the context of the implementation of the NRRP.